Enforcement of Unlicensed Pharmaceutical Distribution: Obstacles, Solutions, and Prosecutor's Perspective - Fitrah Papiah, Gisella Dhea; U. Puluhulawa, Moh Rusdiyanto; Achir, Nuvazria (Estudiante Law Journal, 2024)
Cracking down on the circulation of pharmaceutical preparations without a distribution permit is a serious challenge for the prosecutor's office in Indonesia, given its negative impact on public health and the legal system. This article aims to analyze the obstacles faced by prosecutors in handling illegal pharmaceutical cases and offer strategic solutions to strengthen the effectiveness of law enforcement. The research was conducted using normative juridical methods with conceptual and legislative approaches to evaluate the applicable legal framework, institutional roles, and regulatory relevance to the practical needs of law enforcement. The results of the study revealed that the prosecutor's office faces various obstacles, including a lack of technical understanding by prosecutors related to health law, weak coordination with institutions such as the Food and Drug Supervisory Agency (BPOM) and the police, and limited infrastructure such as accredited forensic laboratories. In addition, existing regulations are considered inadequate in providing a deterrent effect, considering that light sanctions are often not proportional to the negative impact caused by the circulation of illegal pharmaceuticals. This is exacerbated by low public participation in reporting violations and monitoring the distribution of illegal pharmaceutical products. To overcome these obstacles, this study recommends several strategic measures, including strengthening technical capacity through special training for prosecutors, establishing a specialist unit in the prosecutor's office, and integrating coordination between institutions through clear cooperation protocols. Another solution is the use of information technology to create an integrated supervision system, as well as regulatory revisions that tighten sanctions for illegal pharmaceutical actors. This study concludes that strengthening the role of the prosecutor's office requires a comprehensive approach, including institutional reform, cross-sectoral collaboration, and public education. The results of this research are expected to make a practical and academic contribution in improving the effectiveness of law enforcement in the pharmaceutical sector and protecting public health in a sustainable manner.